Total phenolic and antioxidant activities of Pouteria campechiana fruit parts - Kong, Kin Weng; Khoo, Hock Eng; Prasad, Krishnamurthy Nagendra; Chew, Lye Yee; Ismail, Amin (Penerbit Universiti Kebangsaan Malaysia, 2013)
This study aimed to evaluate the total phenolics and antioxidant capacities of the seeds, pulp and peel of Pouteria campechiana fruit using three extraction solvents (water, 70% methanol and 70% ethanol). Among them, 70% ethanol exhibited the best solvent for yielding highest total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activities. The results showed that 70% ethanol extract from the peel contained the highest TPC(2304.7 mg gallic acid equivalent/100 g dw) while the pulp has the highest TFC(6414.03 mg rutin equivalent/100 g dw). The antioxidant activities of the pulp and peel ethanolic extracts were high as determined using 2,2’-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation assay (49.60 and 49.56 mmoL TE/100 g dw) and ferric reducing antioxidant power assay (43.88 and 42.94 Fe2+/100 g dw) but not for seeds. However, their diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activities were ~88%. Thus, the pulp and peel of P. campechiana fruit can be utilized as natural source for antioxidant components.